Effects of Mid-Gestation Nutrient Restriction, Realimentation, and Parity on the Umbilical Hemodynamics of the Pregnant Ewe - Vasquez-Hidalgo, Manuel A.; Swanson, Kendall C.; Vonnahme, Kimberly A. (Frontiers in Animal Science, 2022)
Previous studies have reported that nutritional restriction from d 50 to 130 applied in young nulliparous ewes reduces umbilical blood flow (UBF). We hypothesized that during restriction, UBF and fetal and placentome dimensional measurements would decrease compared to adequately fed ewes, but upon realimentation, ewes would have similar UBF as ewes that were not restricted. We also hypothesized that multiparous ewes would be more resilient to nutrient restriction compared to nulliparous ewes. In experiment 1, second parity Dorset ewes carrying singletons were assigned to an adequate nutrition group (CON, n=7) or a restricted (60% of CON) group (RES, n=8), from d 50 to 90 of gestation. In experiment 2, on d 50 of gestation, adult (15 mo) nulliparous (NUL; n=12) and multiparous (MUL; n=16) Dorset ewes carrying singletons were randomly assigned to receive 100% of NRC recommendations (CON) or 60% of CON (RES). On d 90, all ewes were fed 100% of nutritional recommendations according to body weight. Ewe body weight and conceptus measurements via ultrasonography were recorded every 10 days from d 50 to 130 of gestation. We measured 10 random placentomes, fetal biparietal and abdominal length, kidney length and width. Doppler mode was used to obtain UBF, pulsatility index (PI) and resistance index (RI). Lamb weight and parturition problems were recorded. In experiment 1, on d 80, UBF decreased (P≤0.05, means separation of unprotected F test), placentome size tended to decrease (P≤0.10), and PI and RI tended to increase in RES vs CON ewes (P≤0.10). In experiment 2, there were no three-way interactions or main effects of treatments on UBF, PI, RI and placentome size (P≥0.57). There was a parity by day interaction (P<0.05) for RI, but UBF was not affected by parity or diet. After realimentation, there was no effect of treatment on ultrasound measurements in both experiments. At birth, lambs and placental measurements were not different (P≥0.43). Restriction from d 50 to 90 does not seem to influence umbilical hemodynamics or conceptus growth in adult white face sheep, regardless of parity.